Planning In-service Training Programme: Report of a Need Assessment Survey - Vijayan K (Voices of Teachers and Teacher Educators, 2016)
The present paper explains about ‘why’ and ‘how’ of assessing training needs of teachers for finalising the structure of professional development programmes with the help of empirical data. A Need Assessment Questionnaire (NAQ) has been administered to a sample of primary school teachers to collect information regarding the requirements of in-service training in the area of teaching primary mathematics. The analysis of the data shows that teachers require more orientations on student-centred, activity-based learning methods which are appropriate to the primary school level.